Investigating the relationship between covid-19 anxiety and psychological distress among female high school students in Tabriz - Sahar Habibpour (University of Hormozgan, 2023)
This study aims to examine the relationship between COVID-19 anxiety and psychological distress among adolescent female students in Region 6 of Tabriz. The research follows a correlational design, and the population includes all students in Region 6 of Tabriz, totaling 1840 individuals. A sample of 150 participants was selected using convenience sampling (due to the COVID-19 pandemic) based on the nature of the research. Participants completed the psychological distress questionnaire by Kessler and colleagues (2002) and the COVID-19 anxiety questionnaire. Notably, due to the pandemic, the questionnaires were completed through virtual platforms (Telegram, Instagram, and email). Data analysis was performed using stepwise regression analysis to analyze the findings. Assumptions related to data parametricity, including homogeneity of variances and normal distribution, were examined. The results revealed a significant positive relationship between COVID-19 anxiety and psychological distress. This study sheds light on the impact of COVID-19 anxiety on the psychological well-being of adolescent female high school students.